Outcomes of salvage high-dose-rate brachytherapy with or without external beam radiotherapy for isolated vaginal recurrence of endometrial cancer - Sekii, Shuhei; Murakami, Naoya; Kato, Tomoyasu; Harada, Ken; Kitaguchi, Mayuka; Takahashi, Kana; Inaba, Koji; Igaki, Hiroshi; Ito, Yoshinori; Sasaki, Ryohei; Itami, Jun (Journal of Contemporary Brachytherapy, 2017)
Purpose: This study was designed to retrospectively analyze outcomes of high-dose-rate (HDR) brachytherapy, with or without external beam radiotherapy (EBRT), in patients with vaginal recurrence of endometrial carcinoma, and to identify factors prognostic of patient outcomes. Material and methods : The medical records of all patients who underwent HDR brachytherapy for initial recurrence in the vagina of endometrial cancer after definitive surgery between 1992 and 2014 were retrospectively reviewed. All patients underwent either intracavitary brachytherapy (ICBT) or interstitial brachytherapy (ISBT) with or without EBRT. Late toxicity was graded using the EORTC (LENT/SOMA) scale, revised in 1995. Results : Thirty-seven patients were identified. The median follow-up time was 48 months (range: 6-225 months). Of these 37 patients, 23 underwent ICBT, 14 underwent ISBT, and 26 underwent EBRT. Tumor size at first examination of initial relapse was significantly larger in the ISBT than in the ICBT group. The 4-year respective overall survival (OS), local control (LC), and progression-free survival (PFS) rates in the entire cohort were 81.0%, 77.9%, and 56.8%, respectively. The interval between diagnosis of first recurrence and radiotherapy (< 3 months, ≥ 3 months) was a significant predictor of LC and PFS. OS and LC rates did not differ significantly in the ICBT and ISBT groups. Two patients experienced grade 2 rectal bleeding, and four experienced grade 2 hematuria. No grade 3 or higher late complications were observed. Conclusions : Salvage HDR brachytherapy is an optimal for treating vaginal recurrence of endometrial carcinoma with acceptable morbidity. Early radiotherapy, including brachytherapy, should be considered for women who experience vaginal recurrence of endometrial cancer.